2021
DOI: 10.1002/glia.23982
|View full text |Cite
|
Sign up to set email alerts
|

Amphioxus neuroglia: Molecular characterization and evidence for early compartmentalization of the developing nerve cord

Abstract: Glial cells play important roles in the development and homeostasis of metazoan nervous systems. However, while their involvement in the development and function in the central nervous system (CNS) of vertebrates is increasingly well understood, much less is known about invertebrate glia and the evolutionary history of glial cells more generally. An investigation into amphioxus glia is therefore timely, as this organism is the best living proxy for the last common ancestor of all chordates, and hence provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 102 publications
(188 reference statements)
3
23
0
Order By: Relevance
“…We retrieved additional sequences compared to previous work [30] and report their developmental expression patterns in the amphioxus Branchiostoma lanceolatum. Based on an updated phylogeny of deuterostome glycine transporters, this analysis revealed expression of amphioxus glycine transporters in neurons and glial cells, further strengthening the previously proposed homology of amphioxus and vertebrate glial cell populations [36]. However, we found the paralog-specific expression domains of amphioxus and vertebrate glycine transporter genes to be inversed, hinting at a particularly complex evolutionary history of this gene family.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…We retrieved additional sequences compared to previous work [30] and report their developmental expression patterns in the amphioxus Branchiostoma lanceolatum. Based on an updated phylogeny of deuterostome glycine transporters, this analysis revealed expression of amphioxus glycine transporters in neurons and glial cells, further strengthening the previously proposed homology of amphioxus and vertebrate glial cell populations [36]. However, we found the paralog-specific expression domains of amphioxus and vertebrate glycine transporter genes to be inversed, hinting at a particularly complex evolutionary history of this gene family.…”
Section: Introductionsupporting
confidence: 82%
“…Cross-sections of the rhombospinal region of the nerve cord (Fig. 4K-M) showed that GlyT2.1 was expressed by floor plate and ventrolateral ependymal cells [36]. In L1 larvae, GlyT2.1 was faintly expressed in dorsal cells located posteriorly to the frontal eye complex (Fig.…”
Section: Expression Of Glyt Glyt21 and Glyt22 In Developing Amphioxusmentioning
confidence: 95%
See 2 more Smart Citations
“…Recent research in amphioxus has provided considerable knowledge on the mechanisms underlying axial patterning, germline formation, nervous system development, regeneration, genome architecture, and gene regulation (Somorjai et al, 2012a,b;Marlétaz et al, 2018;Lin et al, 2020;Bozzo et al, 2021). Much of this has been facilitated by recent advances in "omics, " including transcriptomics, genomics and single cell, and the advancement of new methodologies including knockdown and microscopy (Escrivà, 2018).…”
Section: Introductionmentioning
confidence: 99%